Alat Pembelajaran Talingcagra untuk Meningkatkan Hasil Belajar Pembuatan Busana Custom Made - Jayaul Khoiriyah (Ideguru: Jurnal Karya Ilmiah Guru, 2022)
To get the result pressing Custom Made clothing that are neat, slippery and smooth generally used seam roll and tailor’s ham, but because the price is relatively expensive making the tool not buyable. Therefore, an innovation was made to make Alja Talingcagra (learning tools for pillows, bolsters, patchwork, and teak wood grajen. Talingcagra is an equipment in the form of small pillows and bolsters made of patchwork and teak wood grajen. This tool used to ironing open seam allowance on the sewing and to ironing on the shaped area to be leveled, so produce clothing pressing that are neat, slippery and smooth. Generally the succes of practice of making custom made clothes is supported by practical tools (learning tools). The purpose of writing this best practice is to improve the learning result of custom made clothing practice for pressing material. The steps to make Talingcagra is to (1) Make pattern, (2) Cut the material, (3) Sewing pillowcases, (4) Fill the bloster pillow with patchwork and teak wood grajen, and (5) Ffinishing. The result learning before used Talingcagra with the highest score 85, the lowest score 50, class average 70,45 and KKM achievement percentage 29,03%. After the students used Talingcagra get the highest score 95, the lowests score 65, and the class average 80,25 and the KKM achievement persentage 83,87. Therefore, Talingcagra can improve the competence of making custom made clothing in pressing material.